A Thousand Words About Modern Medical Education: A Mini-Review Concerning the Theory of Education - Al-Jarshawi, Mustafa Hussein Ajlan; Al-Imam, Ahmed (Journal of Medical Science, 2022)
The present article represents a mini-review and a reflective essay concerning modern medical education methods, as well as ways to adapt them to medical education’s local conditions (disciplines), including basic medical sciences. We introduced Gagné’s theory of learning and other theories – Constructivist, Experiential, and Humanistic – followed by Dennik’s "twelve tips" for effective learning and Harden’s ten questions for curriculum development. Outcome-based education (OBE) was discussed and related to relevant concepts within Miller’s pyramid and Bloom’s taxonomy. Harden’s SPICES model was emphasized concerning education strategies while discussing the assessment of learning (AoL), assessment as learning (AaL), and assessment for learning (AfL). Finally, the authors advise exploring the adaptation of modern education methods for a specific discipline of basic medical sciences – Human Anatomy – by incorporating the abovementioned concepts and integrating different AfL and AaL assessment tools while conveying a graphical concept map for this scenario.